PERANMEDIA SOSIAL TWITTER DALAM INTERAKSI SOSIAL PELAJAR SEKOLAH MENENGAH PERTAMA DI KOTA PEKANBARU (studi kasus pelajar SMPN 1 kota Pekanbaru) - Hasan Basri; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Technological progress in recent years that develops very rapidly gives you a lot an impact on human life , the use of technology is not only to help finish the job the company but already enters social interaction in the community , communities now can interact indirectly but intense only by using facilities and sophistication offered technology now .One of the most near reach the is with the social media .Media social that come through various features provide facilities remarkable for the user , started from the media social provide services message , share photos and videos to offer facilities for users free mengemukan opinion such twitter .On use media social twitter are very popular among the community , not limited age hamper everyone know , use even active in twitter . Including one of them is students, students is the most active whom often use twitter and using it as a share information or just a chirpThe purpose of this research is to get a the extent to which social media uses twitter among all these junior high school students and to see how social interactions who awakes among all these junior high school students by using social media the twitter .By using interksi social theory that explains a great variety of the interaction of a pattern in the community .By using the method deskriftif quantitative it is hoped that this research can provide an illustration that sistematif about this phenomenon .Based on this research , active users in a media social twitter among students junior high school is 41 % of the total sample , this indicates that media social twitter is still very popular for students to do interkasi .And the use of as a means of used to interact with school friends is the percentage the highest .The positive impact of social interaction uses the media twitter of them the students can open widely tissue friendship them that interaction what happened indefinite period of time and space it can be access when and where it .